(untitled) (The Pakistan Development Review, 2006)
Despite various attempts at reforming the civil services the common perception seems to be that the system essentially remains similar to that inherited from the colonial past. Worse still, little is known about the perceptions of civil servants on various issues in civil service reforms. Against this backdrop, the Pakistan Institute of Development Economics conducted a perception survey of civil servants seeking their views on recruitment, training, performance evaluation, job satisfaction, and relationship with the private sector. This preliminary report highlights the key findings of the survey. Section 2 sets out the survey methodology. Sections 3 to 7 respectively highlight the survey findings with respect to recruitment, postings and training, performance evaluation, job satisfaction, bureaucracy, private sector, and institutions and reforms.